Gender, violence and resilience among Ugandan adolescents. (August 2017) - Namy, Sophie; Carlson, Catherine; Norcini Pala, Andrea; Faris, Devin; Knight, Louise; Allen, Elizabeth; Devries, Karen; Naker, Dipak
Abstract: Resilience, commonly understood as the ability to maintain adaptive functioning in the face of adversity, has emerged as a salient entry point in the field of positive youth development. This study makes a unique contribution by exploring dimensions of resilience among adolescents in Uganda, examining associations between violence from different perpetrators and resilience, and testing whether sex moderates these relationships. Analyses are based on data from 3706 primary school students. Exploratory factor analysis (EFA) identified five factors underlying the construct of resilience: Emotional Support; Family Connectedness; School Connectedness; Social Assets; and Psychological Assets. We used regression analysis to investigate associations between these dependent variables, background characteristics, and experiences of violence (including exposure to intimate partner violence against female caregivers). Results reflect a complex relationship between violence and resilience, with patterns varying by perpetrator (e.g., teacher, peers, caregivers) and some evidence that the sex of the student moderates these dynamics. Overall, there is a consistently negative relationship between all violence measures and Psychological Assets. In addition, teacher violence is associated with lower resilience across factors and both caregiver violence and exposure to IPV are consistently associated with decreased Family Connectedness. These findings suggest that adolescents experiencing (and exposed to) violence from adults may be particularly vulnerable to internalizing and/or externalizing behaviors and withdrawal from the family. Findings point to preventing violence from teachers complemented with enhancing family relationships as promising avenues for resilience-strengthening interventions, and also emphasize the need to consider gendered strategies to ensure girls and boys benefit equally.